Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 10 - Radical Expressions and Equations - 10-4 Solving Radical Equations - Practice and Problem-Solving Exercises - Page 624: 41



Work Step by Step

$Given,$ $\sqrt (2y) - \sqrt (y+2)=0$ $\sqrt (2y)-\sqrt (y+2) + \sqrt (y+2) = \sqrt (y+2)$ $\sqrt (2y)=\sqrt (y+2)$ Squaring, $2y=y+2$ $2y-y=2$ $y=2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.